2020
DOI: 10.1080/13574809.2020.1819781
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental safety? Exploring experienced safety in relation to other qualities of successful public spaces

Abstract: Combining insights from the urban design and criminological literature, this paper explores the degree to which conviviality, feeling welcome, and feeling at home are related to peoples' experiences of safety. A questionnaire was distributed on four squares in the city of Utrecht, the Netherlands. While participants valued the positive qualities of the squares differently, feeling safe was connected to a wider, positive evaluation of the quality of space and especially to feeling at home. By investing primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Brands. B and others [10] summarized what is a good quality public space. There are four qualities: accessible for people are engaged in activities there; comfortable, a good image; and sociable place, where people meet each other and take people when they come to visit.…”
Section: Importance Of Interior Public Spacesmentioning
confidence: 99%
“…Brands. B and others [10] summarized what is a good quality public space. There are four qualities: accessible for people are engaged in activities there; comfortable, a good image; and sociable place, where people meet each other and take people when they come to visit.…”
Section: Importance Of Interior Public Spacesmentioning
confidence: 99%
“…Perceived safety is the degree to which individuals feel safe within an environment (Hedayati Marzbali et al, 2021;Hedayati-Marzbali et al, 2017;Abdullah et al, 2021). Perceived safety in public spaces is a dimension of quality of place connected to feelings of being welcome (Brands et al, 2020). Studies have suggested environmental quality as a key dimension of place quality (Källström and Hultman, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%